Profil Kemampuan Literasi Matematika Siswa SMK dalam Menyelesaikan Soal Geometri Berdasarkan Perbedaan Kemampuan Awal - Nurpratiwi, Tigas Laila; Ardani, Dyah Ayu Puspita; Munawaroh, Elys Qotrunnada (Jurnal Riset Pendidikan dan Inovasi Pembelajaran Matematika, 2023)
Mathematical literacy is an vital portion of building 21st-century abilities. This think about pointed to look at the scientific proficiency capacity profile of professional understudies in tackling geometric issues concurring to their starting numerical capacities. This inquire about may be a clear ponder employing a subjective approach. The devices utilized in this consider were an introductory numerical capacity test, a scientific education test, and an meet direct. The subjects of this ponder were three understudy course of X review understudies from each category, to be specific understudies with tall, medium, and moo starting scientific capacities. The comes about of this consider were understudies with tall introductory numerical capacities were able to total all markers of the definition, application, and translation forms; understudies with direct beginning numerical capacities can as it were total the definition and application pointers; students with low initial math ability not all indicators can be achieved. Out of the three categories, students with higher initial mathematical skills performed the best in mathematical literacy.